2017
DOI: 10.1128/aem.02766-16
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic Acid and Its Taurine- or Glycine-Conjugated Species Reduce Colitogenic Dysbiosis and Equally Suppress Experimental Colitis in Mice

Abstract: The promising results seen in studies of secondary bile acids in experimental colitis suggest that they may represent an attractive and safe class of drugs for the treatment of inflammatory bowel diseases (IBD). However, the exact mechanism by which bile acid therapy confers protection from colitogenesis is currently unknown. Since the gut microbiota plays a crucial role in the pathogenesis of IBD, and exogenous bile acid administration may affect the community structure of the microbiota, we examined the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 76 publications
10
74
0
Order By: Relevance
“…Sato et al ., have shown that UDCA exerts its preventive effect on DSS‐induced colitis through its bacterial conversion into LCA, which is a TGR5 agonist . In addition, Van den Bossche et al ., showed that UDCA ameliorates DSS‐induced colitis in mice by improving colitogenic dysbiosis in the colon . This also supports the present observation that BB, which contains abundant UDCA (Table ), increased both UDCA and LCA content in the cecum and exerted ameliorative effects on DSS‐induced colitis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Sato et al ., have shown that UDCA exerts its preventive effect on DSS‐induced colitis through its bacterial conversion into LCA, which is a TGR5 agonist . In addition, Van den Bossche et al ., showed that UDCA ameliorates DSS‐induced colitis in mice by improving colitogenic dysbiosis in the colon . This also supports the present observation that BB, which contains abundant UDCA (Table ), increased both UDCA and LCA content in the cecum and exerted ameliorative effects on DSS‐induced colitis.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the animal bile preparations containing different types of bile acid are assumed to exert distinct effects on the pathophysiology of gastrointestinal tissues. Indeed, the beneficial effects of bile acids in animal bile preparations have been recently demonstrated using a dextran sulfate sodium (DSS)‐induced colitis model , which is extensively used as an experimental model of inflammatory bowel diseases . No study, however, has yet examined whether the animal bile preparations have therapeutic efficacy against inflammatory bowel disease experimentally or clinically.…”
Section: Introductionmentioning
confidence: 99%
“…For example, UDCA ameliorates DSS-induced colitis in mice, and this is associated with expansion of antiinflammatory enteric bacterial species, including cluster XIVa Clostridium and Akkermansia muciniphila, which are generally depleted in IBD patients. 158,159 Whether the therapeutic effects of UDCA in rodent colitis models is translatable to human IBD patients, and the extent to which this activity involves direct effects on hepatic BA production, the gut flora, and/or the mucosal immune system remains to be elucidated. Nonetheless, these data raise the possibility that elevated BA accumulation in the intestinal mucosa, due to either altered BA metabolism or increased intestinal permeability, contribute to IBD-associated mucosal inflammation.…”
Section: The Implications: Targeting Bile Acids and Their Receptors Imentioning
confidence: 99%
“…Bile acids are also bacterial metabolites with pleotropic functions, including the regulation of metabolism and inflammation through interactions with both microbial and host receptors [60]. Ursodeoxycholic acid, a hydrophilic secondary bile acid, ameliorates mouse experimental colitis by expanding anti-inflammatory cluster XIVa Clostridium and Akkermansia muciniphila [61]. Dysbiosis in enteric bacteria changes bile acid receptor FXR expression, which is protective for experimental colitis models through inhibiting NF-kB signaling [62].…”
Section: Dysbiosis-associated Mucosal Immune-dysfunction In Ibdmentioning
confidence: 99%